Development of Digital-Based Ethnomathematics E-Modules to Improve Mathematical Literacy - Chika Rahayu; Pradnyo Wijayanti; Mazia Aulia Azizah; Riza Haikal Azhar (Universitas Negeri Surabaya, 2026)
The lack of mathematical literacy skills and the importance of using e-modules in geometry learning are the background of this study. This research aims to develop a digital-based ethnomathematics e-module that is valid, practical, and effective in improving students' mathematical literacy. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 30 junior high school students in grade VIII. The instruments used included expert validation sheets, student response questionnaires, and mathematical literacy tests. The results of the study show that the e-modules developed have a high level of validity based on the assessment of material experts and media experts. In addition, the e-module is stated to be practical based on positive student responses, as well as effective in improving mathematical literacy as shown by improving student test results categorized medium category. Thus, digital-based ethnomathematics e-modules are suitable for use as an alternative teaching material to support contextual and meaningful mathematics learning.